Immune Checkpoint Inhibitors: Anti-NKG2A Antibodies on Board. Issue 2 (February 2019) - Mingari, Maria Cristina; Pietra, Gabriella; Moretta, Lorenzo
Abstract : Antibodies directed towards checkpoint inhibitors have unveiled extraordinary potential in cancer therapy. An article by the Vivier group ( Cell 2018;175:1731–1743) shows that blocking the HLA-E-specific NKG2A inhibitory receptor, expressed by NK and inducible in T cells, results in benefits against poor prognosis tumors. Moreover, NKG2A and PD-1/PD-L1 mAb combinations unleash tumor-specific T cell proliferation and memory.